Material Immateriality: the Skins’ Discourse - Ceriani , Giulia (E|C, 2023)
In the measure which currently willingly favors the discussion on materials – their nature, their recycling – over that on shapes, the question of dematerialization arises with great force. Either of a materiality that is only an effect, when it concerns the representation within the digital universes. What happens to those expressive substances that refer to some form of physicality (i.e. silk or leather), when they are brought back to a pure effect in a digital context? Does this deal with a visual transcoding only, or there is something more? If the same expressive substances are called to dress an actorial identity in a digital world, are they just to be considered as a last development of the mutation of materials that we have been witnessing for years, or they represent a specific case of mediatization? Are we just faced to the overturn of our perceptual habits, expectations and criteria of appreciation, or are we attending, by the ongoing development of Metaverse, to unprecedented manifestations of a world still under construction? This reflection aims to investigate the different aspects inherent to the evolution of materiality, up to its physical dissolution (immaterial materiality), and to understand how much -and if- the semiotic tools we have at our disposal can help us.